K.H.E. ABDURRAHMAN AND FORMULATION OF CADRE EDUCATION IN PERSATUAN ISLAM’S BOARDING SCHOOLS - Ridwan, Ridwan; Fauzan, Pepen Irpan; Fata, Ahmad Khoirul (State Islamic University North Sumatra, 2021)
Abstract: This present study discusses the boarding school-based regeneration in Persatuan Islam (PERSIS) organization formulated by KH. Endang Abdurrahman during the period of 1954-1983. Historical approach is employed in this study with qualitative descriptive model. It reveals that cadre management is culturally performed, where direct and personal relationship between teacher and students are formed. In its development, PERSIS regeneration is more organized through educational institution: Pesantren (Islamic Boarding School) owned by PERSIS and courses for Muballigh or preacher. Historically, this reinforcement gained its momentum when PERSIS was led by KH. E. Abdurrahman from 1962 to1983.The system developed by Abdulrahman was yet exclusive and unintegrated with the national education system. Through such system, PERSIS was able to produce many religious scholars (muballigh and ustadz).Keywords: PERSIS, cadres management, PERSIS Pesantren, K.H.E. Abdurrahman